Philippines - Tope, Lily Rose R. 1955-; Nonan-Mercado, Detch P.; Yong, Jui Lin. (New York Marshall Cavendish, 2013)
"Provides comprehensive information on the geography, history, wildlife, governmental structure, economy, cultural diversity, peoples, religion, and culture of the Philippines"--Provided by publisher.
Philippines today -- Geography -- History -- Government -- Economy -- Environment -- Filipinos -- Lifestyle -- Religion -- Language -- Arts -- Leisure -- Festivals -- Food -- Map of the Philippines -- About the economy -- About the culture -- Time line -- Glossary.
Includes bibliographical references and index.
Keywords: Philippines -- Juvenile literature; Literature